Two Canine Papillomaviruses Associated With Metastatic Squamous Cell Carcinoma in Two Related Basenji Dogs. (November 2016) - Luff, J.; Rowland, P.; Mader, M.; Orr, C.; Yuan, H.
Papillomaviruses (PV) are associated with benign mucosal and cutaneous epithelial proliferations. In dogs, PV-associated pigmented plaques and papillomas can undergo malignant transformation, but this is rare, and most cases of canine squamous cell carcinoma do not arise from PV-induced precursor lesions. We describe herein the progression of pigmented plaques to invasive and metastatic squamous cell carcinoma associated with 2 canine papillomaviruses (CPV) in 2 related Basenji dogs. Immunohistochemistry for PV antigen revealed strong nuclear immunoreactivity within keratinocytes from pigmented plaques from both dogs, consistent with a productive viral infection. Polymerase chain reaction (PCR) using degenerate primers for the L1 gene revealed PV DNA sequences from 2 different CPVs. In situ hybridization for CPV revealed strong hybridization signals within the pigmented plaques and neoplastic squamous epithelial cells from both dogs. We report here progression of PV-associated pigmented plaques to metastatic squamous cell carcinoma within 2 Basenji dogs associated with 2 different CPVs.